Social Studies’ Teaching in the Era of Quality Education - González Sánchez, David (2020)
This essay explores the basic principles of quality education’s discourse and the skill-based learning model and the impact on social studies subject-matter and therefore on the way in which the subject considers the relationship between historical knowledge, citizenship and thought. To support these ideas, I review the current education policy, the national curriculum and the curriculum of the subject. The result is a brief characterization on three issues: the distortion of thought relegated to skills, the confusing theoretical foundation of the program to adapt categories such as historical time and geographical space to the demands of the skills curriculum and the technification of learning.